Investigação e análise do comportamento informacional de alunos participantes de empresas juniores no Brasil - Marco Antonio Carvalho Brum (2008)
This work analyzes the information behavior of member students of junior enterprises in Brazil. The study explored the search behavior of junior enterprise students. Fourteen sources were analyzed in terms of their frequency of use, relevance and reliability. Moreover, it was investigated the usefulness of these sources for learning, sharing, problem-solving, project development, service to customers and storage.Two hundred and seventy answers were analyzed, and the survey quantitative method was used.The results show that personal sources (work colleagues) are accesses more frequently and considered more relevant, either through the Internet or in direct contacts for a simple conversation. The most reliable sources for them are books and professors. The students also answered that they use information sources mainly for learning and sharing information with other people.